2000
DOI: 10.4049/jimmunol.165.10.5954
|View full text |Cite
|
Sign up to set email alerts
|

Triggering FCα-Receptor I (CD89) Recruits Neutrophils as Effector Cells for CD20-Directed Antibody Therapy

Abstract: CD20 Abs induce clinical responses in lymphoma patients, but there are considerable differences between individual patients. In 51Cr release assays with whole blood as effector source, RAJI cells were effectively killed by a mouse/human chimeric IgG1 construct of CD20 Ab 1F5, whereas ARH-77 proved resistant to killing by this Ab. When whole blood was fractionated into plasma, mononuclear cells, or granulocytic effector cells, RAJI cells were effectively killed in the presence of complement-containing plasma, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
85
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 107 publications
(89 citation statements)
references
References 40 publications
3
85
0
1
Order By: Relevance
“…Neutrophils were also shown to contribute to the anti-tumor ADCC in Non-Hodgkin's Lymphoma using antibodies to CD20 (Rituximab) [341], in breast cancer using a Tn antigen-specific chimeric mAb [342], and in B-cell lymphoma using a bispecific singlechain fragment variable-specific for HLA class II and FcαRI (CD89) [343]. The bispecific antibody against the myeloid receptor for IgA (FcαR1; CD89) and the B-cell surface marker CD20 induced neutrophil-dependent ADCC toward broad range of B cell lines [344]. Lysis via FcαRI:CD20 bispecific antibodies was enhanced in blood from patients during therapy with G-CSF or GM-CSF [344].…”
Section: Antibody-dependent Cell-mediated Cytotoxicity (Adcc)mentioning
confidence: 99%
See 1 more Smart Citation
“…Neutrophils were also shown to contribute to the anti-tumor ADCC in Non-Hodgkin's Lymphoma using antibodies to CD20 (Rituximab) [341], in breast cancer using a Tn antigen-specific chimeric mAb [342], and in B-cell lymphoma using a bispecific singlechain fragment variable-specific for HLA class II and FcαRI (CD89) [343]. The bispecific antibody against the myeloid receptor for IgA (FcαR1; CD89) and the B-cell surface marker CD20 induced neutrophil-dependent ADCC toward broad range of B cell lines [344]. Lysis via FcαRI:CD20 bispecific antibodies was enhanced in blood from patients during therapy with G-CSF or GM-CSF [344].…”
Section: Antibody-dependent Cell-mediated Cytotoxicity (Adcc)mentioning
confidence: 99%
“…The bispecific antibody against the myeloid receptor for IgA (FcαR1; CD89) and the B-cell surface marker CD20 induced neutrophil-dependent ADCC toward broad range of B cell lines [344]. Lysis via FcαRI:CD20 bispecific antibodies was enhanced in blood from patients during therapy with G-CSF or GM-CSF [344]. Interestingly, Otten et al [345] observed that immature neutrophils mobilized from the bone marrow upon G-CSF treatment, efficiently triggered tumor cell lysis via FcαRI (CD89), but were unable to initiate tumor cell killing via FcγR.…”
Section: Antibody-dependent Cell-mediated Cytotoxicity (Adcc)mentioning
confidence: 99%
“…Restoration of deposition of C3b(i) on target cells may increase the immunotherapeutic action of RTX, even when complement-mediated lysis does not occur. Several lines of evidence suggest that recognition of RTXopsonized cells by Fc␥ receptors on phagocytic cells promotes ADCC and contributes to RTX immunotherapeutic action (10,(15)(16)(17)(18). Opsonization of IgG-containing target cells with C3b activation products enhances Fc␥ receptor-mediated phagocytosis of cells by both neutrophils and monocytes (38,39).…”
Section: Complement and Rtxmentioning
confidence: 99%
“…The efficacy of this mAb in indolent or follicular NHL is well documented, and it is also being examined as an immunotherapeutic agent against chronic lymphocytic leukemia (CLL) (7)(8)(9)(10). The mechanism of antitumor activity of RTX in vivo remains a subject of some debate; preclinical studies, as well as more recent reports of animal models and clinical investigations have provided support for apoptosis (11)(12)(13)(14), Fc␥ receptor-mediated Ab-dependent cellular cytotoxicity (ADCC) (10,(15)(16)(17)(18), and complement-dependent cytotoxicity (CDC) (19 -28). In patients selected for treatment based on relatively low circulating lymphocyte counts (Ͻ5000/ l), infusion of RTX leads to rapid and prolonged depletion of normal and malignant B cells from the bloodstream (1,4).…”
mentioning
confidence: 99%
“…Surprisingly, PMNs were able to effectively kill a broad range of B cell lines mediated by a (FcaRI 3 CD20) bsAb (22). However, also with FcaRI as trigger molecule, PMNs were still not able to lyse malignant B cell lines via CD19 or CD37-directed chemically linked bsAbs.…”
mentioning
confidence: 99%